The Effectiveness of Wordwall-Based Gamification on Students’ Vocabulary Mastery and Students’ Perceptions Towards Its Implementation in Learning English Vocabulary - Yulia Komalasari; Lalu Thohir; Desi Herayana (Jurnal Ilmiah Profesi Pendidikan, 2026)
Students' perceptions are important because they influence how learners respond to teaching methods, learning media, and classroom activities. Therefore, examining both vocabulary achievement and students' perceptions can provide a more comprehensive understanding of Wordwall implementation in English learning. This study investigated the use of Wordwall-based gamification in improving students' vocabulary mastery and examined students' perceptions of its implementation in English vocabulary learning. The study employed a quantitative approach with a pre-experimental one-group pre-test and post-test design. The participants were 25 tenth-grade students from the Electrical Engineering 1 class (X TE-1) at SMK Negeri 2 Gerung. Data were collected through vocabulary tests and a students' perception questionnaire. The data from the vocabulary test were examined through descriptive statistics, a normality assessment, and the Wilcoxon Signed-Ranks Test as the scores from the post-test did not follow a normal distribution. The results indicated that the average score for students rose from 29.80 in the pre-test to 72.00 in the post-test. The Wilcoxon assessment revealed a notable difference between the pre-test and post-test outcomes, Z = -4.376, p < .001. Every one of the 25 students achieved improved scores in the post-test, with no negative rankings or ties present. The questionnaire results also indicated positive to very positive perceptions of Wordwall, particularly in terms of ease of use, affective engagement, usefulness, and learning engagement. These findings suggest that Wordwall-based gamification can support vocabulary learning and create a more enjoyable and engaging classroom atmosphere. However, because this study used a pre-experimental design without a control group, the results should be interpreted as evidence of improvement associated with the intervention rather than definitive causal proof.